BURNOUT AMONG GENERATION Z: RISK FACTORS AND COPING STRATEGIES - Umy Yonaevy; Endang Sri Wahyuni (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Burnout is a condition of physical, emotional, and mental exhaustion that is increasingly experienced by Generation Z due to pressure in the workplace, academics, and social life. This study aims to identify the main risk factors that contribute to burnout among Generation Z and the coping strategies that can be used to overcome it. The risk factors found include excessive workload, social pressure due to digital media, economic instability, and lack of balance between personal and professional life. Meanwhile, effective coping strategies include good time management, social support, mindfulness, and implementing limits on technology use. This study emphasizes the importance of the role of individuals, educational institutions, and organizations in creating an environment that supports the mental well-being of Generation Z.